Supporting Digital Administration and Finance Competencies for BESIK's Wiralodra University Management in 2024: Towards Transparency and Efficiency in Student Organizations - Cahyanto, Iman (PT FORMOSA CENDEKIA GLOBAL, 2024)
This training focuses on applying digital technology in student organizations' administrative and financial management, aiming to enhance efficiency, transparency, and collaboration within organizational management. The critical concepts explored include digitalization, particularly the utilization of Google Drive and Google Sheets, and their impact on the quality of organizational governance. The study employs a focused discussion method, engaging 20 administrators from UKM BESIK's at Wiralodra University for the 2024-2025 academic year during a training session held on October 16, 2024. The results indicate that digitalization enhances the effectiveness of financial and document management and strengthens coordination and accountability. These findings hold significant implications for other student organizations seeking to develop a technology-based management system that fosters a more transparent and professional organizational culture